2006
DOI: 10.1007/11790853_35
|View full text |Cite
|
Sign up to set email alerts
|

Feature Analysis and Classification of Classical Musical Instruments: An Empirical Study

Abstract: is one of six departments that make up the School of Business at the University of Otago. The department offers courses of study leading to a major in Information Science within the BCom, BA and BSc degrees. In addition to undergraduate teaching, the department is also strongly involved in postgraduate research programmes leading to MCom, MA, MSc and PhD degrees. Research projects in spatial information processing, connectionist-based information systems, software engineering and software development, informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Christian et al [14] did empirical study on feature analysis for instrument recognition and found nineteen features selected from the Mel-frequency cepstral coefficients (MFCC) and the MPEG-7 audio descriptors achieved a recognition rate of around 94% by the best classifier assessed by cross validation. Liu [4] did a similar work finding the modified k-NN classifier compared to other ones such as GMMs using 19 features, in which 6 are temporal, 8 are spectral, and 5 are coefficients, achieves the highest accuracy of 93%.…”
Section: Related Workmentioning
confidence: 99%
“…Christian et al [14] did empirical study on feature analysis for instrument recognition and found nineteen features selected from the Mel-frequency cepstral coefficients (MFCC) and the MPEG-7 audio descriptors achieved a recognition rate of around 94% by the best classifier assessed by cross validation. Liu [4] did a similar work finding the modified k-NN classifier compared to other ones such as GMMs using 19 features, in which 6 are temporal, 8 are spectral, and 5 are coefficients, achieves the highest accuracy of 93%.…”
Section: Related Workmentioning
confidence: 99%
“…In the absence of an universally agreed set of music features on which to base classification, researchers have chosen their own feature sets, including those dealing with frequency, pitch, loudness and other aspects of spectral content. The same features are also typically used for polyphonic recognition [14]. Feature-based approaches using fuzzy clustering [15] and rule-based approaches [16] have also been tried.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the learning procedure is evaluated by classifying new sound samples (cross-validation). One of the most crucial aspects in the above procedure of instrument classification is to find the right features [2] and classifiers. Most of the research on audio signal processing has been focusing on speech recognition and speaker identification.…”
Section: Introductionmentioning
confidence: 99%